Fragment fryzu kamiennego znalezionego w Et-Tell, Izrael - Skupińska-Løvset, Ilona (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
Present article deals with a block of basalt found on Et-Tell, identified with biblical Bethsaida. The block is only partially preserved and has today the dimensions: length 105,5 cm and 83 cm, height varying from 38 cm to 36,6 cm, depth between 46 cm and 36,5 cm. From the shape of the fragment and from the placement of the decoration it may be deduced that the stone formed originally a lintel. Decoration is carefully executed by use of the small-calibrated claw-chisel. It consists of a meander pattern with the motives of rosettes. Alternately a whirling rosette and a still standing are placed between the arms of meander. It is argued, on the stylistic and iconographical reasons, that the lintel should be dated to the Augustean period. There is pointed out on intensified influence of Roman art and culture during the reign of Herod the Great and his heirs. Further, the analysed motif of meander is compared to the similar motifs on basalt architecture of Hauran and Golan and the limestone architecture of nearby settlements of Galilee.